Concept and Implementation of Innovative Scalable Wind Turbine Emulator with Doubly Fed Asynchronous Machine - Robert Rink; Robert Małkowski; Bartłomiej Gawin; Klara Janiga (Energies)
This paper presents the design of an innovative scalable wind turbine emulator. The system’s hardware and software components are described in detail including test results, demonstrating the research potential of the proposed design. The uniqueness of the proposed solution lies in its scalability, achieved despite the use of physical devices with fixed parameters. This scalability allows for the flexible shaping of the system’s structure and parameters, allowing it to emulate both individual wind turbines with a capacity ranging from kilowatts to megawatts as well as aggregated models of entire wind farms. The emulator was developed using the hardware-in-the loop (HIL) concept and consists of a digital part including aerodynamic and mechanical models (wind, rotor, shaft models, disturbances, etc.) and control systems for mechanical and electrical devices within the wind turbine. The digital component has a modular structure, which allows for the replacement of any module of the native control system with the user’s custom designed one and testing its properties over a broad range of parameters. The test results presented in the article demonstrate a satisfactory level of accuracy of the developed emulator.